Audit Results Quality: The Role of Competency, Independency, Auditor Ethics, and Due Professional Care - Susilowati, Endah (Indonesian Journal of Sustainability Policy and Technology, 2023)
Public accountants, in carrying out their profession, are required to produce quality audits. Several factors must support the auditor, both from within and outside the auditor. Factors originating from within the auditor that can influence the quality of audit results include competence, knowledge, level of education, work experience, independence, accountability, due professional care, objectivity, integrity, and ethics. Meanwhile, factors external to an auditor include obedience pressure, audit fees, and task complexity. This research aims to analyze the influence of competency, independence, auditor ethics, and due professional care on the quality of audit results. This research uses Partial Least Square (PLS) to analyze these variables' relationships. The primary data were collected using questionnaires to auditors in the public accounting firms (KAP) in Surabaya, East Java, Indonesia. Based on the analysis and discussion in the previous section, it can be concluded that the auditor's competence, independence, and ethics have been proven to affect the quality of audit results significantly. Meanwhile, Due Professional Care has been proven to negatively affect the quality of audit results significantly. KAP is expected to be able to increase the experience of each auditor in conducting audits and to maintain an attitude of competence, independence, auditor ethics, and due professional care so that the quality of the resulting audit results will be better.